Burning rubber or burning out? The influence of role stressors on burnout among truck drivers - Judith Semeijn; Barry De Waard; Wim Lambrechts; Janjaap Semeijn (Logistics, 2019)
Professional truck drivers are prone to both physical and psychological stress. Such stress can lead to burnout. Drawing on Job Demands Resources literature and stress research, we investigate the relationship between job related role stressors and three components of burnout, among professional truck drivers who are based in the Netherlands. They were surveyed with a time-lagged design (interval of two months). In the first wave, the different potential causes of burnout were measured (role conflict, role ambiguity, quality of sleep, and the perceived emotional intelligence of the dispatcher). In the second wave, the three elements of burnout were measured: emotional exhaustion, depersonalization, and low personal accomplishment. The results of our study indicate that role conflict relates positively to all three components of a burnout. The emotional intelligence of the dispatcher—as perceived by the truck drivers—was negatively related with the three components of a burnout. Finally, the quality of sleep had an impact on depersonalization and emotional exhaustion. Theoretically, several job specific role stressors are confirmed to play a role in truck driver burnout. However, the top three role stressors all appeared to be related to the trucking industry, instead of a particular employer, and they may therefore require national policy measures.
Keywords: 650; burnout; perceived emotional intelligence; quality of sleep; role stressors; truck drivers